An analysis of cultural elements in selected festive advertisements - Ismail Sualman,; Nuurrianti Jalli,; Razween Md Rashidi,; Darwis, Yuliandre (Penerbit Universiti Kebangsaan Malaysia, 2021)
Cultural knowledge and understanding are fundamental in a multiracial society like Malaysia. One of the ways to foster a good relationship between people of different cultural backgrounds can be achieved through the use of media. One of the means of such a message that could be disseminated to the public is through festive advertisements. Previous studies have shown that the portrayal of culture in ads is a pivotal element that should be considered by all advertisers in producing festive advertisements. This study aims to explore whether the content of festive advertisements in Malaysia portray and deliver messages that could potentially assist in fostering a good relationship between races in Malaysia. A quantitative content analysis was done on ten festive ads. These ads were selected based on pre-determined criteria – 1) ads have to be produced by a local company, 2) uploaded on YouTube, and 3) related to the festive season. For this research, a festive ad is defined as advertisements related to festivals celebrated by the Malaysian community. Research results revealed that the majority of the selected festive ads for this study portrayed positive values that could assist in fostering good relations among people of different cultural backgrounds. The element of togetherness has been used across different festive ads to intensify the need for cross-cultural understanding, especially during festive seasons.